Molecular and cytogenetic analyses of cryptic species within the Synbranchus marmoratus Bloch, 1795 (Synbranchiformes: Synbranchidae) grouping: species delimitations, karyotypic evolution and intraspecific diversification - Utsunomia, Ricardo; Pansonato-alves, José C.; Costa-silva, Guilherme J.; Mendonça, Fernando F.; Scacchetti, Priscilla C.; Oliveira, Claudio; Foresti, Fausto (Sociedade Brasileira de Ictiologia, 2014)
The fish species Synbranchus marmoratus has been reported to exist as a species complex due to high intraspecific karyotypic variability in spite of the difficulty or impossibility to distinguish them using morphological traits alone. The goal of this work was to use cytogenetic and molecular methods to determine the species delimitations and understand the karyoevolution of S. marmoratus using samples collected from distinct Brazilian localities. Among the analyzed specimens, a large degree of cytogenetic variation related to diploid numbers and karyotype structure was observed, with karyotypes showing 2n=42, 44 and 46 chromosomes. In addition, using sequences of three mitochondrial genes, the phylogenetic relationships between every sample with a known karyotype were determined, which revealed significant nucleotide divergence among the karyomorphs. Also, the analyses indicate that chromosomal rearrangements occurred independently within the distinct lineages of S. marmoratus complex, which resulted in the appearance of distinct karyotypic variants in a non-linear fashion related to diploid numbers and in the appearance of similar non-homologous chromosomes. Finally, the integration of both molecular cytogenetic and phylogenetic approaches allowed the determination of specific chromosomes possibly involved in rearrangements and a better understanding about the evolutionary processes involved in the differentiation of Synbranchus genus.

A espécie de peixe Synbranchus marmoratus tem sido reportada como um complexo de espécies devido à elevada variabilidade cariotípica intraespecífica a despeito da dificuldade ou impossibilidade de distingui-las usando apenas caracteres morfológicos. O objetivo deste trabalho foi utilizar métodos citogenéticos e moleculares para determinar a delimitação das espécies e compreender a carioevolução de S. marmoratus utilizando amostras coletadas em distintas localidades brasileiras. Dentre os espécimes analisados, um alto grau de variação citogenética relativo aos números diploides e estrutura cariotípica foi observado, com cariótipos mostrando 2n=42, 44 e 46 cromossomos. Adicionalmente, utilizando sequências de três genes mitocondriais, as relações filogenéticas entre cada amostra com cariótipo conhecido foram determinadas, revelando uma divergência nucleotídica significativa entre os cariomorfos. Além disso, as análises indicam que rearranjos cromossômicos ocorreram independentemente nas distintas linhagens do complexo S. marmoratus, o que resultou no aparecimento de distintas variantes cariotípicas de forma não linear em relação aos números diploides e no surgimento de cromossomos similares e não homólogos. Finalmente, a integração de uma abordagem citogenética molecular e filogenética permitiu a determinação de cromossomos específicos que, possivelmente, estão envolvidos em rearranjos e um melhor entendimento sobre os processos evolutivos envolvidos na diferenciação do gênero Synbranchus.
Keywords: Chromosomal diversity; Fish cytogenetics; Karyotype evolution; Repetitive DNA; Species complex